Clinicopathological features and prognostic validity of the European Neuroendocrine Tumor Society (ENETS) and American Joint Committee on Cancer (AJCC) 8th staging systems in colonic neuroendocrine neoplasms - Yu Zhang; Liang Shang; Pan‐Pan Zhang; Luo‐Hai Chen; Wei Wang; Cheng Fang; Meng Qiu; Xing‐Yu Feng; Lin Zhou; Meng Zhang; Huang‐Ying Tan; Xu‐Dong Qiu; et al. (Cancer Medicine, 2019)
Abstract Purpose This study aimed to investigate the characteristics of colonic neuroendocrine neoplasms (NENs) and to validate the prognostic value of the European Neuroendocrine Tumor Society (ENETS) and American Joint Committee on Cancer (AJCC) 8th staging systems. Methods A total of 167 and 1248 patients with colonic NENs from 12 medical centers across China and from the Surveillance, Epidemiology, and End Results (SEER) cancer registry in the United States, respectively, were reviewed. Patients were staged according to the ENETS and AJCC 8th staging systems. Results Clinicopathological features of colonic NENs in the Chinese cohort and SEER cohort were significantly distinct. In both the Chinese cohort and the SEER cohort, colonic neuroendocrine carcinoma (NEC) and mixed adeno‐neuroendocrine carcinoma (MANEC) were more frequent in the midgut than in the hindgut. Tumors originating from the midgut tended to be larger and at a more advanced stage than those from the hindgut. The AJCC 8th staging system and the ENETS system appeared to have similar prognostic ability for colonic NEC/MANEC. Conclusions Our study revealed that tumors originating from the midgut and the hindgut shared different clinicopathological features. The AJCC 8th staging system and the ENETS system appeared to have similar prognostic ability for colonic NEC/MANEC.